Examining the Food Security Status, Weight, and Sociodemographic Factors of Pantry Clients - Walch, Amanda (Curr Dev Nutr, 2020)
OBJECTIVES: To examine the relationship between food security, weight, and sociodemographic factors of food pantry clients. METHODS: A cross-sectional study with clients from the largest food pantry in Alaska. Recruitment was February - March of 2018 over different times of the day, week, and month. A total of 148 clients filled out a sociodemographic questionnaire and the U.S. Adult Food Security Survey Module. RESULTS: Over half of the participants were over the age of 55 years (50.4%), were female (60%), not married or living with a partner (67%), and were a high school graduate/equivalent (72%). The main ethnic populations were Caucasian (37.8%), Alaska Native/American Indian (25.7%), and Asian/Pacific Islander (12.8%). The majority of participants were either overweight (31%) or obese (39%). Most were employed at least part time (72%), had an annual income of less than $25,000 per year (59%), and visited the food pantry monthly (65%). Over 88% % of participants were food insecure (45% low food security and 43% very low food security). Chi-square and a multivariate logistic regression determined associations between sociodemographic characteristics and stratified food security status or weight category. Analyses were performed using SPSS with a P-value of </=0.05, although no significant associations were found. Despite the non-significant findings, the pantry has made changes to aid in the high rates of food insecurity and obesity. The pantry is now providing information to their clients for other emergency food provisions across town. Staff have moved the nutrient-rich foods to eye level to encourage healthy choices. A table for extra produce is available where clients can chose up to double their allowable amounts. A limit has been set on the desserts to reduce the amount of sugar. The pantry is seeking donated foods that are high in fiber and low in sugar. CONCLUSIONS: Food insecurity among food pantry clients is high at 88%, compared to the local rate of 12.3%. However, clients’ weight and food security status were not associated and by continuing to provide emergency food assistance while not addressing underlying causes of food insecurity or obesogenic factors, rates will likely not improve. FUNDING SOURCES: A grant from the Center for Community Engagement and Learning at the local University.